The Effect of Temephos to Mortality and Life Level of Aedes aegypti mosquitoes - Firda Yanuar Pradani (Insights in Public Health Journal, 2020)
Temephos is an insecticide active ingredient often used by a community as Dengue Hemorrhagic Fever (DHF) vector control in imago. The development of Ae aegypti is influenced by biotic and abiotic factors. This study aimed at determining the effects of temephos concentration on mortality and a life level of Ae aegypti at some concentration tests.The experimental design used in this study was Complete Random Design (CRD). This study involved temephos as the active ingredient and third instar Ae. Aegypti larvae originating from Pangandaran Regency. Data analysis used an ANOVA test with 5 treatments and 5 replications. The results showed that there was any influence of concentration towards a number of mortality, a life level, morphology of larvae, pupae and imago, a number of males and females, and a number of eggs hatchability. Temephos concentration affected the mortality of third instar larvae of Ae. aegypti with temephos concentration of 0.019 ppm, 0.069 ppm, 0.105 ppm, and 0.140 ppm and affected a life level of Ae. aegypti with biological parameters.